Postcolonialism and science fiction - Langer, Jessica, 1982- (Palgrave Macmillan, 2011)
Postcolonialism and Science Fiction explores intersections and interactions between the genre of science fiction and the theory and practice of postcolonialism, concentrating primarily on contemporary science fiction from the 1950s to the present day. The book argues that several of the foundational myths of science fiction -- the 'other', or the stranger, and the strange and foreign land -- are shared at the heart of colonialism, and that postcolonial science fiction has developed unique and creative ways of overcoming and dispelling these myths. Using close readings and thematic studies, ranging from lively discussions of Japanese and Canadian science fiction to a thorough and incisive deconstruction of race and (post)colonialism in the online game World of Warcraft, Postcolonialism and Science Fiction is the first comprehensive study of the complex and developing relationship between the two areas. It will be of interest to fans, researchers, students and anyone else interested in science fiction, postcolonial studies, or both.